Desempenho de um painel fotovoltaico de baixa tensão, acoplado ao protótipo de um conversor dc/dc topologia Booster - Alcântara, Sara Maria Freitas de (2010)
Low voltage solar panels increase the reliability of solar panels due to reduction of in series associations the configurations of photovoltaic cells. The low voltage generation requires DCDC converters devices with high efficiency, enabling raise and regulate the output voltage. This study analyzes the performance of a photovoltaic panel of Solarex, MSX model 77, configured to generate an open circuit voltage of 10.5 V, with load voltage of 8.5 V, with short circuit current of 9 A and a power of 77 W. The solar panel was assembled in the isolated photovoltaic system configuration, with and without energy storage as an interface with a DCDC converter, Booster topology. The converter was designed and fabricated using SMD (Surface Mounted Devices) technology IC (integrated circuit) that regulates its output voltage at 14.2 V, with an efficiency of 87% and providing the load a maximum power of 20.88 W. The system was installed and instrumented for measurement and acquisition of the following data: luminosities, average global radiation (data of INPE Instituto Nacional de Pesquisas Espaciais), solar panel and environment temperatures, solar panel and DC-DC converter output voltages, panel, inverter, and battery charge output currents. The photovoltaic system was initially tested in the laboratory (simulating its functioning in ideal conditions of operation) and then subjected to testing in real field conditions. The panel inclination angle was set at 5.5°, consistent with the latitude of Natal city. Factors such as climatic conditions (simultaneous variations of temperature, solar luminosities and ra diation on the panel), values of load resistance, lower limit of the maximum power required by the load (20.88 W) were predominant factors that panel does not operate with energy efficiency levels greater than 5 to 6%. The average converter efficiency designed in the field test reached 95%